Comparative Analysis of Lycorine in Wild Plant and Callus Culture Samples of Hymenocallis littoralis by HPLC-UV Method - Subramaniam, Sreeramanan; Sundarasekar, Jeevandran; Sahgal, Geethaa; Murugaiyah, Vikneswaran (Hindawi Publishing Corporation, 2014)
The Hymenocallis littoralis, an ornamental and medicinal plant, had been traditionally used for wound healing. In the present study, an analytical method using HPLC with ultraviolet detection was developed for the quantification of lycorine in the extracts of different parts of wild plant and tissue culture samples of H. littoralis.The separationwas achieved using a reversed-phase column. The method was found to be accurate, repeatable, and sensitive for the quantification of minute amount of lycorine present in the samples. The highest lycorine content was found in the bulb extract (2.54 ± 0.02